Impactos da expansão da cana-de-açúcar: percepção e prática científica - Passos, Haihani Silva (2015)
Brazil has been through a significant expansion of sugar cane production by incorporating new cultivation areas from the second half of 2000 decade. The existence of a research structure able to develop new cultivars adopted to local soil and climate conditions was necessary. Literature about expansion process presents environmental, social and economic impact. Therefore, the main aim of this research is to identify how technologic innovation developing researchers see their innovation impact and incorporate this perception on their own technology production. The following research question was formulated: how do technologic innovation developers from sucroenergetic sector anticipate themselves from possible environmental and socioeconomic impacts? Do scientists’ perceptions of possible impacts influence knowledge production? To answer these questions, research groups from two institutions were analyzed: Rede Interuniversitária para o Desenvolvimento do setor Sucroalcooleiro (RIDESA) and Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA). In order to develop this research, the following data collection techniques were used: field research, using open and non-directed interviews. Content analysis technique was adopted to qualitative data analysis. The general conclusion of this research is that in both cases (RIDESA and EMBRAPA), researches are aware of possible research impacts. The idea is not to evaluate if researchers perception is right or wrong or if their reality view is correct, but, above all, to understand that they have their own reality perception and that this perception interferes in their scientific practice.